The Definitive Guide to NetBeans™ Platform - Böck, Heiko (Apress, 2013)
This book is aimed at Java developers wanting to create desktop applications on top of the NetBeans Platform. No knowledge of the NetBeans Platform is assumed. The primary goal of this book is the practical explanation of the basic concepts and functionalities of the NetBeans Platform. In the process, you will be introduced to the great support for this kind of development offered by the NetBeans IDE. You will hopefully begin asking yourself why you haven’t been developing your desktop applications on top of a platform all along! At the very least, you will learn about the many advantages you could have benefited from in your past Java programming activities.